Pengaruh Penggunaan Media Pembelajaran Online (whatsapp dan Zoom) Terhadap Prestasi Belajar Siswa Pada Masa Pandemi Covid-19 - Naning Eko Noviana; M Riadhos Solichin (Universitas Negeri Surabaya, 2021)
The objective of this study to determine the effect of the use of online learning media on student's learning achievement in the covid-19 pandemic. The sample in this study used a random sample from class XI Accounting 1 dan 2 SMK Kemala Bhayangkari 1 Waru Sidoarjo The research approach used in this research is quantitative research. Regression analysis in this study using SPSS 21.0 for windows software. The results showed that the use of online learning media had a positive effect on student achievement during the Covid-19 pandemic.